Implementation of advanced control methods for flyback converters - Loh, Jonathan Wei Jun (2019)
This final year project aims to design and implement advanced control methods to regulate flyback converter and investigate its regulation performance. An in-depth study will be done on the flyback converters as well as the advanced control methods. The advanced control methods that will be used to investigate its regulation performance are Proportional-Integral (PI) Control and Model Predictive Control (MPC) methods. Using different voltage references to examine the controller responds when the flyback converter is conducting in both buck and boost mode. The results from the simulation of flyback using both advanced control methods show that MPC is a better choice over PI control in regulating the flyback converter.